Calcium-dependent enzyme activation and vacuole formation in the apical granular region of pancreatic acinar cells - Raraty, Michael (The National Academy of Sciences, 2000)
The pancreatic acinar cell produces powerful digestive enzymes packaged in zymogen granules in the apical pole. Ca(2+) signals elicited by acetylcholine or cholecystokinin (CCK) initiate enzyme secretion by exocytosis through the apical membrane. Intracellular enzyme activation is normally kept to a minimum, but in the often-fatal human disease acute pancreatitis, autodigestion occurs. How the enzymes become inappropriately activated is unknown. We monitored the cytosolic Ca(2+) concentration ([Ca(2+)](i)), intracellular trypsin activation, and its localization in isolated living cells with specific fluorescent probes and studied intracellular vacuole formation by electron microscopy as well as quantitative image analysis (light microscopy). A physiological CCK level (10 pM) eliciting regular Ca(2+) spiking did not evoke intracellular trypsin activation or vacuole formation. However, stimulation with 10 nM CCK, evoking a sustained rise in [Ca(2+)](i), induced pronounced trypsin activation and extensive vacuole formation, both localized in the apical pole. Both processes were abolished by preventing abnormal [Ca(2+)](i) elevation, either by preincubation with the specific Ca(2+) chelator 1,2-bis(O-aminophenoxy)ethane-N,N-N′,N′-tetraacetic acid (BAPTA) or by removal of external Ca(2+). CCK hyperstimulation evokes intracellular trypsin activation and vacuole formation in the apical granular pole. Both of these processes are mediated by an abnormal sustained rise in [Ca(2+)](i).